2002
DOI: 10.1038/sj.onc.1205467
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation regulates the stability of the regulatory CK2β subunit

Abstract: Protein kinase CK2 is a protein serine/threonine kinase that exhibits elevated expression in a number of cancers and displays oncogenic activity in mice. The regulatory CK2b subunit has a central role in assembly of functional tetrameric CK2 complexes where it participates in modulation of catalytic activity and substrate speci®city. Since overexpression of CK2b results in elevated levels of CK2 activity, we investigated the molecular mechanisms that control its degradation since perturbations in these pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 77 publications
4
71
0
7
Order By: Relevance
“…In addition, phosphomimicking in the human CK2b subunit enhances its stability (Zhang et al, 2002). In line with this result, we found that rice CK2b3 contains a related "destruction" box (YDYALDLILD) in the analogous position (amino acids 139 to 148), and abundance of CK2b3 was reduced when it was dephosphorylated in Pi-starved plants.…”
Section: Phosphorylation Of Pts Is Dependent On Pi Supplysupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, phosphomimicking in the human CK2b subunit enhances its stability (Zhang et al, 2002). In line with this result, we found that rice CK2b3 contains a related "destruction" box (YDYALDLILD) in the analogous position (amino acids 139 to 148), and abundance of CK2b3 was reduced when it was dephosphorylated in Pi-starved plants.…”
Section: Phosphorylation Of Pts Is Dependent On Pi Supplysupporting
confidence: 79%
“…Treatment with MG132 (10 mM), a 26S proteasome inhibitor, blocked the CK2b3 decline but not the reduction in phosphorylation ( Figure 2D), indicative of protein degradation dependent on the ubiquitin/26S proteasome pathway. CK2b subunits that fail to form complexes with catalytic subunits are rapidly degraded (Zhang et al, 2002). In this context, the reduced accumulation of CK2b3 we observed under Pi starvation suggested that unphosphorylated CK2b3 may display decreased binding affinity with CK2a3 to form a stable holoenzyme.…”
Section: Ck2a3/b3-mediated Phosphorylation Of Pts Under Pi-sufficientmentioning
confidence: 86%
“…Moreover, transfection with Chk1 alone leads to an increase of endogenous CK2b ( Figure 2a, lane 2). It is known that CK2b degradation is mediated by the proteosome (Zhang et al, 2002). The fact that coexpression of CK2b with Chk1 leads to enhanced CK2b expression, might indicate a protective role of Chk1 with respect to CK2b degradation via the proteosome pathway.…”
Section: Chk1 Is a Ck2b Interacting Partnermentioning
confidence: 99%
“…Moreover, CK2 is physiologically expressed at a higher level than CK2 , and the excess of the regulatory subunit is rapidly ubiquitinated and degraded in a proteasomedependent manner (Luscher & Litchfield, 1994;Zhang et al, 2002). To protect CK from the degradation machinery and to stabilize it, six surface-exposed lysine residues were mutated to arginine (French et al, 2007).…”
Section: Mutation Of Ck2β That Affects Its Stabilitymentioning
confidence: 99%